Simple Scan Tests for Spatial Clustering on a Square Lattice. Issue 2 (10th April 2013) - Rogerson, Peter A.; Wang, Le
<x xml:space="preserve">Abstract</x> Many data sets collected for study areas consist of data values collected on a square lattice or for a set of pixels. Remotely sensed data provide perhaps the most common example. Frequently, we wish to know whether there are subregions of the study area that exhibit spatial clustering. In this article, we suggest how an approach for finding spatial clusters may be combined with the common practice of using 3‐by‐3 and 5‐by‐5 smoothing filters or kernels to construct two simple and easy‐to‐implement scan‐type tests. A simulation experiment shows that the power of these tests to find clusters compares favorably with an alternative test that is more complicated. The tests use simulated data, changes in a remotely sensed image for a study region in Texas, and data about wheat yields. Muchas bases de datos que se recopilan para una zona de estudio, consisten en valores recopilados en una retícula cuadrada o en un conjunto de pixeles. Los datos obtenidos por sensores remotos son quizá el ejemplo más común. Frecuentemente deseamos saber si existen subregiones de la zona de estudio que exhiban agrupamiento espacial. En este artículo, sugerimos cómo una aproximación para ubicar agrupamientos espaciales se puede combinar con la práctica común de usar filtros de suavizado (kernels) de 3‐por‐3 y 5‐por‐5 filtros, para construir dos test tipo scan, sencillos y fáciles de implementar. Un experimento de simulación demuestra que el poder de estas pruebas para ubicar agrupamientos, se compara favorablemente frente a otra prueba alternativa, que resulta más complicada. Las pruebas usan datos simulados, cambios en una imagen de satélite para un área de estudio en Texas, y con data acerca de los rendimientos de cultivos de trigo. 研究区收集的许多数据集是由基于方格网和像素采集的数据值组成的，遥感数据可能提供了最常见的范例。通常，我们希望了解研究区的子区域是否呈现空间集聚特征。本文提出了一种如何发现空间集聚的方法，可以与采用3*3和5*5平滑滤波或核函数的普通试验相结合，构造两个简单且易于操作的扫描试验。模拟实验结果显示，这些试验在寻找聚集特征的性能上优于更复杂的可替换性试验。文中所用的仿真模拟数据来源于德克萨斯州小麦产量的多时相遥感影像。